Jackson, Robert H. & Rosberg, Carl G., Personal Rule in Black Africa Prince, Autocrat, Prophet, Tyrant, Berkeley/Los Angeles/London, University of California Press, 1982, 316 pp. - Serrano López, Lilia (Estudios de Asia y África, 1983)
-